Comparison of QFT-IT and QFT-Plus for Detecting Latent Tuberculosis in HIV-Infected Iranian Patients - Abtahian, Zahra; Eghbal, Elaheh; Tabarsi, Payam; Khalili, Farima; Nasiri, Mohammad Javad (Novelty in Biomedicine, 2025)
Background: Tuberculosis (TB) is a major public health issue, especially among Human immunodeficiency virus (HIV)-infected individuals, where early detection of latent tuberculosis infection (LTBI) is crucial. Interferon-gamma release assays (IGRAs), like quantiferon-TB gold "in tube" (QFT-IT) and QFT-Plus, are more accurate alternatives to the tuberculin skin test (TST). This study compares the diagnostic performance of QFT-IT and QFT-Plus for detecting LTBI in HIV patients in Iran. Materials and Methods: A cross-sectional study was conducted at Masih Daneshvari Hospital, Iran’s national tuberculosis center, between 2020 and 2023. HIV-infected individuals were tested using both QFT-IT and QFT-Plus assays. Agreement between the two tests was evaluated using the kappa coefficient, and McNemar's test was used to assess discrepancies. Results: Of the 100 HIV-infected patients, 93% demonstrated agreement between the two tests. However, 7% of participants showed discrepancies, with six patients testing negative on QFT-Plus but positive on QFT-IT. The kappa coefficient for agreement was 0.92, indicating high concordance between the two assays. McNemar's test revealed no significant difference in diagnostic performance. Conclusion: Both QFT-IT and QFT-Plus exhibited strong agreement in detecting LTBI in HIV-infected Iranian patients, supporting their use as reliable diagnostic tools for LTBI screening in this population. Further studies are recommended to assess their utility in other settings and patient populations.